Mind-Wandering Changes in Dysphoria - Guesdon, Alice; Lejeune, François-Xavier; Rotgé, Jean-Yves; George, Nathalie; Fossati, Philippe (Frontiers in Psychiatry, 2020)
Changes in mind-wandering (MW) and involuntary autobiographical memory (IAM) in dysphoria have been explored with conflicting results. The aim of this study was to evaluate both MW and IAM in a group of 23 stable dysphoric participants compared to 37 controls, and to compare their thoughts characteristics (ie. specificity, visual perspective, time orientation, emotional valence). To make this study comparable with previous research we used two different monotonous vigilance tasks (with and without verbal interference stimuli).Our results showed a significantly greater focus on mind-wandering thoughts in dysphoria. The characteristics of spontaneous thoughts content did not differ significantly between our dysphoric participants and controls, which is not in favor of strong emotional dysfunction. Our results suggest a difficulty to regulate the occurrence of self-generated thoughts rather than their content, that may confer to dysphoric subjects increased cognitive risk to develop a major depressive episode.